Arthur's lost library book - Brown, Marc Tolon; WGBH (Television station : Boston, Mass.); CINAR Productions Inc.; Sony Wonder (Firm); Random House Video (New York : Sony Wonder : Random House Home Video, 2004)
Arthur's lost library book: In the first story, Arthur can't find the scary library book he checked out. D.W.'s imaginary friend: Much to Arthur's embarrassment, D.W. has invented an imaginary friend. When D.W. brings "Nadine" to the amusement park, Arthur learns that even imaginary friends, and little sisters, aren't always so bad. D.W.'s library card: After finally getting her first library card, Arthur's little sister D.W. tries to check out her favorite book, with humorous results.
Arthur's lost library book -- D.W.'s imaginary friend - - D.W.'s library card.
Title from container.
Collection of 3 episodes of the PBS television show.
Based on the Arthur adventure books by Marc Brown.
MPAA rating: Not rated.
DVD; Dolby digital.
Closed-captioned.
Keywords: Arthur (Fictitious character : Brown) -- Juvenile films; D.W. (Fictitious character) -- Juvenile films; Books and reading -- Juvenile films; Animation -- Television; Children's -- Television